Sacred Values? The Effect of Information on Attitudes toward Payments for Human Organs - Elias, Julio J.; Lacetera, Nicola; Macis, Mario (American Economic Review, 2015)
Are attitudes about morally controversial (and often prohibited) market transactions affected by information about their costs and benefits? We address this question for the case of payments for human organs. We find in a survey experiment with US residents (N=3,417) that providing information on the potential efficiency benefits of a regulated price mechanism for organs significantly increased support for payments from a baseline of 52 percent to 71 percent. The survey was devised to minimize social desirability biases in responses, and additional analyses validate the interpretation that subjects were reflecting on the case-specific details provided, rather than just reacting to any information.